2000
DOI: 10.1046/j.1523-1747.2000.00133.x
|View full text |Cite
|
Sign up to set email alerts
|

The OTF3 Gene Polymorphism Confers Susceptibility to Psoriasis Independent of the Association of HLA-Cw*0602

Abstract: Psoriasis has been strongly associated to HLA-Cw6, but it remains unclear whether Cw6 itself or a closely linked gene is associated with the disease. The aim of this study was to clarify whether the HLA-C itself determines disease susceptibility or whether it acts only as a marker for the susceptibility allele. We examined a sample of 95 type I psoriasis patients and 104 Spanish matched controls to investigate whether HLA-Cw*0602 or other closely related class I loci, such as HLA-B and MICA (which are centrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
2
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 38 publications
(44 reference statements)
1
36
2
1
Order By: Relevance
“…Although such an interpretation may be the correct one at times, many other MHC genes deserve attention as alternative explanations for HLA associations. Some investigators have considered these non-HLA genes [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and these efforts would be facilitated by better characterization of the relationships among these MHC genes.…”
Section: Introductionmentioning
confidence: 99%
“…Although such an interpretation may be the correct one at times, many other MHC genes deserve attention as alternative explanations for HLA associations. Some investigators have considered these non-HLA genes [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and these efforts would be facilitated by better characterization of the relationships among these MHC genes.…”
Section: Introductionmentioning
confidence: 99%
“…Since the penetrance of HLA-Cw*0602 is only about 10%, it has been proposed that other genomic segments near the HLA-C locus might be also involved in determining PV susceptibility [3]. POU5F1 gene, located 96 kb telomeric to the HLA-C locus, is considered a possible psoriasis candidate gene because of its location within the PSORS1 locus [4,5]. POU5F1 is a sequence-specific transcription factor essential for keeping embryonic stem cells in a pluripotent status [6], and the activation of POU5F1 results in dysplastic growths in epithelial tissues [7].…”
Section: Dear Editormentioning
confidence: 99%
“…The POU5F1 gene has been noted as being expressed in embryonic stem cells and tumor cells but not in differentiated tissues. Previous studies have shown that the POU5F1 +1377T (formerly called OTF3-B) allele is strongly associated with psoriasis in the Caucasian population [4,5]. However, until now, no comprehensive study of all exonic single nucleotide polymorphisms (SNPs) of POU5F1 gene has been documented in Chinese patients with PV.…”
Section: Dear Editormentioning
confidence: 99%
“…However, except in some isolated studies none of these candidates have associated more strongly than HLACw*0602 across diverse populations (13)(14)(15)(16)(17)(18)(19)(20). Therefore we have continued the screening for new candidates in the area between HLA-C and P0U5F1.…”
mentioning
confidence: 99%